Peculiarities of interaction between transport infrastructure and economic growth - Micevičiene, Diana; Bazaras, Žilvinas (Univerzita Pardubice, 2010)
The link between transport infrastructure and economic development has to play a significant role in the development of transport network plans in any country. In fact, the relationship between investment in transport infrastructure and economic development has been the subject of investigation for quite some time. Despite this, the subject remains mired in controversy. The difficulty of establishing the relationship between transport and economy is that numerous other factors influence this relationship. The process of economic development, where besides transport other factors play a part, must have a central place in a consideration of transport and economy. This paper, based on recent exploration of the authors, examines the question whether and under what conditions developed transport infrastructure engender economic activity. The paper explains the nature of the problem and describes the foundations of the possible interrelation between the effects themselves. Seeking to analyze the effects and alternatives of their evaluation in more compressive manner, the authors of the article present firstly initiative processes of interaction between transport infrastructure and economic growth, secondly mechanism of their development in producing economic environment. The results of empirical testing of the model are also presented.
Keywords: transport; infrastructure; effects; cost; economic growth; measurement